CORRELATION BETWEEN LABORATHORY PARAMETERES AND COVID-19 TREATMENT OUTCOME - Radojevic-Marjanovic, Ruzica; Jankovic, Slobodan; Krstic, Kristijan; Opancina, Valentina D (Medicinski časopis, 2021)
Objective. The aim of this study was to explore the baseline characteristics and correlation of the C-reactive protein, D-dimer, Ferritin and human serum albumins, with the treatment outcome of COVID-19 infection. Methods. Our study was conducted in the Clinic for infectious diseases at the University Clinical Center Kragujevac during the time frame from November 1st 2020 to February 1st 2021. It was designed as case series and it included patients of age greater than 18 years and positive Polymerase Chain Reaction test or serological (antigen) test on SARS-COV-2 who were treated at our clinic. Results. A significant correlation was found between human serum albumins (g/L) with the outcome variable p=0.009, while correlation coefficient was 0.466. Also lower level of albumins was significantly correlated with the intrahospital mortality, whereas p=0.007 and correlation coefficient was 0.484. Conclusion. Our study results suggest that hypoalbuminemia could be possibly used as a significant prognostic factor for intrahospital mortality in COVID-19 patients.